2014
DOI: 10.1089/jmf.2013.2889
|View full text |Cite
|
Sign up to set email alerts
|

Korean Red Ginseng Improves Glucose Control in Subjects with Impaired Fasting Glucose, Impaired Glucose Tolerance, or Newly Diagnosed Type 2 Diabetes Mellitus

Abstract: This study was designed to evaluate the effect of Korean red ginseng (KRG) supplementation on glucose control in subjects with impaired fasting glucose (IFG), impaired glucose tolerance (IGT), or newly diagnosed type 2 diabetes mellitus (T2DM). The study was a 12-week randomized, double-blinded, placebo-controlled (5 g of KRG [n = 21] or placebo [n = 20] in tablet form) trial. Glucose-related biomarkers, including serum and whole blood levels of glucose, insulin, and Cpeptide, were measured by 2-h oral glucose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 15 publications
(17 reference statements)
1
54
1
Order By: Relevance
“…Subjects were randomized in a double-blind, placebo-controlled trial. The trial results showed that 12 weeks of intervention with KRG supplementation (5 g/ day) led to normalization of whole blood and serum glucose levels as well as serum insulin and CRP concentrations (Bang et al, 2014). Administration of Panax Ginseng extract (PGE) for 8 weeks (6 g/day) decreased serum triglycerides and total cholesterol and LDL levels, while increasing HDL levels.…”
Section: Ginseng To the Clinicmentioning
confidence: 99%
“…Subjects were randomized in a double-blind, placebo-controlled trial. The trial results showed that 12 weeks of intervention with KRG supplementation (5 g/ day) led to normalization of whole blood and serum glucose levels as well as serum insulin and CRP concentrations (Bang et al, 2014). Administration of Panax Ginseng extract (PGE) for 8 weeks (6 g/day) decreased serum triglycerides and total cholesterol and LDL levels, while increasing HDL levels.…”
Section: Ginseng To the Clinicmentioning
confidence: 99%
“…Our previous study indicated that KRG supplementation was efficacious for glucose control [12]. Therefore, we applied a similar study design for this randomized, double-blind, and placebo-controlled clinical trial to evaluate the effect of AF supplementation on blood glucose control in subjects with IFG, IGT, or newly diagnosed type 2 diabetes mellitus (T2DM).…”
Section: Introductionmentioning
confidence: 99%
“…produced through the fermentation process. As reported by Bang et al in the clinical trial [20], 5 g/day of Korean red ginseng can reduce fast blood glucose and glucose AUC. However, in this study [21], the fermented red ginseng only modulated postprandial glucose and insulin, not fasting glucose and insulin.…”
Section: Anti-diabetic Effects Of Ginseng In Human Trialsmentioning
confidence: 55%
“…Participants with impaired fasting glucose, impaired glucose tolerance, or type 2 diabetes consuming 5 g/day Korean red ginseng (KRG) extract were found to have significantly reduced blood glucose. Specifically, −1.23 ± 0.59 mmol/L of serum glucose and -0.97 ± 0.30 mmol/L of whole blood glucose were decreased at a 30 min oral glucose tolerance test after a 12-week intervention [20]. The plasma insulin sensitivity index increased by 33% compared to the placebo group in this 12-week randomized, double-blind and placebo-controlled trial [20].…”
Section: Anti-diabetic Effects Of Ginseng In Human Trialsmentioning
confidence: 78%